Description of the first new species of Leuctridae (Plecoptera) from Jiangsu Province of China - Chen, Zhi-Teng; Du, Yu-Zhou (Zootaxa, 2017)
The first new species of Leuctridae (Plecoptera) from Jiangsu Province of eastern coastal China, Rhopalopsole vespertilio sp. nov. is described and illustrated. The new species belongs to the R. magnicerca species group and is distinguished by the bat-like shaped central plate of tergum 10, by the medially narrowed subtrapezoidal transverse bars, and by the upcurved hook formed by the small epiproct. The new species is compared with similar taxa.